Funcionalidade global de idosos hospitalizados - PEREIRA, Esdras Edgar Batista (Universidade Federal do Pará, 2017)
Objective: Identify the global functionality of hospitalized elderly, correlating the performance to basic (BADL) and instrumental (IADL) activities of daily life, with the main functional systems (cognition, mood, mobility and communication). Methods: Analytical, observational, cross-sectional study, with the participation of 94 elderly patients admitted to a medical clinic. The tools used in the assessments were: the Katz Scale, Lawton and Brody Scale, Mini-Mental State Examination (MMSE), Geriatric Depression Scale 15 (GDS-15), Timed Up and Go Test (TUG) and the Functional Assessment of Communication Skills from the American Speech-Language-Hearing Association (ASHA FACS). Results: 94 elderly people were evaluated, where most had some degree of dependence for BADL (61.71%) and IADL (52.13%). In functional systems, autonomy proved to be preserved with an average performance of 18.14 points on the MMSE, and 4.43 points in the GDS-15; independence was altered, for average performance of 21.82 seconds on the TUG, classifying them with regular mobility, and 5.27 points in ASHA FACS, considering them as in need of moderate assistance in this task. It was evidenced moderate and significant association between performance for IADL and BADL in nearly all functional systems. Conclusion: The study population presented changed overall functionality, due to some degree of dependence in BADL and IADL, with preserved autonomy and impaired independence. The correlations showed that with the decline of the major functional systems occurred decline in overall functionality.